Answer:
the point-slope form of the equation: y + 3 = -³/₂(x - 2)
the slope-intercept form of the equation: y = -³/₂x
standard form of the equation: 3x + 2y = 0
Explanation:
![\bold{slope\, (m)=(change\ in\ Y)/(change\ in\ X)=(y_2-y_1)/(x_2-x_1)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/2zs5rsimzrs7su64ca25jtnl033msvjwuq.png)
(-2, 3) ⇒ x₁ = -2, y₁ = 3
(2, -3) ⇒ x₂ = 2, y₂ = -3
So the slope:
![\bold{m=(-3-3)/(2-(-2))=\frac{-6}4=-\frac32}](https://img.qammunity.org/2022/formulas/mathematics/high-school/ixc2krsbzgw72hf31b53l6yiua3y3wqq87.png)
The point-slope form of equation is : y - y₀ = m(x - x₀), where (x₀, y₀) is any point the line passes through.
(2, -3) ⇒ x₀ = 2, y₀ = -3
Therefore:
y + 3 = -³/₂(x - 2) ← the point-slope form of the equation
y + 3 = -³/₂x + 3
y = -³/₂x ← the slope-intercept form of the equation (b=0)
y + ³/₂x = 0
3x + 2y = 0 ← standard form of the equation